The Role of the CpG Island Methylator Phenotype on Survival Outcome in Colon Cancer - Kang, Ki Joo (Gut Liver, 2015)
BACKGROUND/AIMS: CpG island methylator phenotype (CIMP)- high colorectal cancers (CRCs) have distinct clinicopathological features from their CIMP-low/negative CRC counterparts. However, controversy exists regarding the prognosis of CRC according to the CIMP status. Therefore, this study examined the prognosis of Korean patients with colon cancer according to the CIMP status. METHODS: Among a previous cohort population with CRC, a total of 154 patients with colon cancer who had available tissue for DNA extraction were included in the study. CIMP-high was defined as 3/5 methylated markers using the five-marker panel (CACNA1G, IGF2, NEUROG1, RUNX3, and SOCS1). RESULTS: CIMP-high and CIMP-low/negative cancers were observed in 27 patients (17.5%) and 127 patients (82.5%), respectively. Multivariate analysis adjusting for age, gender, tumor location, tumor stage and CIMP and microsatellite instability (MSI) statuses indicated that CIMP-high colon cancers were associated with a significant increase in colon cancer-specific mortality (hazard ratio [HR], 3.23; 95% confidence interval [CI], 1.20 to 8.69; p=0.02). In microsatellite stable cancers, CIMP-high cancer had a poor survival outcome compared to CIMP-low/negative cancer (HR, 2.91; 95% CI, 1.02 to 8.27; p=0.04). CONCLUSIONS: Regardless of the MSI status, CIMP-high cancers had poor survival outcomes in Korean patients.